1999
DOI: 10.1021/es990220g
|View full text |Cite
|
Sign up to set email alerts
|

Iodide Sorption to Subsurface Sediments and Illitic Minerals

Abstract: Laboratory studies were conducted to quantify and identify the key processes by which iodide (I-) sorbs to subsurface arid sediments. A surprisingly large amount of I- sorbed to three alkaline subsurface sediments that were low in organic matter content; distribution coefficients (K d's) ranged from 1 to 10 mL/g and averaged 3.3 mL/g. Experiments with pure mineral isolates, similar to the minerals identified in the clay fraction of the sediments, showed that there was little or no I- sorption to calcite (K d =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 25 publications
4
108
2
1
Order By: Relevance
“…The calculated Kd values vary from 0.02 to 0.09 L/kg. On the one hand, these values appear much lower than those proposed by Kaplan et al (2000) with values varying between 46 to 22 L/Kg as the pH value increased from 3.6 to 9.4. On the other hand, these values appear coherent with the work of Tournassat et al (2007).…”
Section: Comparison Of Iodide Accessible Porosity and Nmr Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…The calculated Kd values vary from 0.02 to 0.09 L/kg. On the one hand, these values appear much lower than those proposed by Kaplan et al (2000) with values varying between 46 to 22 L/Kg as the pH value increased from 3.6 to 9.4. On the other hand, these values appear coherent with the work of Tournassat et al (2007).…”
Section: Comparison Of Iodide Accessible Porosity and Nmr Resultscontrasting
confidence: 69%
“…The sorption of iodide on synthetic montmorillonite and MX-80 bentonite can be neglected (Kaplan et al, 2000). For illite, in conditions relevant to nuclear waste repositories in clay formations (pH~7, ionic strength ~ 0.1 M), contradictory results are found in the literature: it is considered either significant with Kd values around 20 L/kg (Kaplan et al, 2000) or weak with Kd values expected below 1 L/kg (Tournassat et al, 2007). To assess the importance of this sorption parameter, porosities were estimated for the two model phases as a function of parameters affecting sorption, i.e.…”
Section: Comparison Of Iodide Accessible Porosity and Nmr Resultsmentioning
confidence: 99%
“…In addition, because iodide adsorption was close to zero on sediments that contained a high percentage of Fe oxide, iodide adsorption was not significantly influenced by Fe oxide content in the sediments. Instead, iodide adsorption might be more related to clay mineral content, especially illite as found by Kaplan et al (2000).…”
Section: Distribution Coefficient (K D ) Measurementsmentioning
confidence: 92%
“…Organic iodo compounds are not soluble and form readily through reaction with I 2 and, to a lesser extent, I - (Lieser and Peschke, 1982;Couture and Seitz, 1985); retention of iodine in soils is mostly associated with the organic matter (Wildung et al, 1974;Muramatsu, et al, 1990;Gu and Schultz, 1991;Yoshida et al, 1998;Kaplan et al, 2000). Several studies have suggested that fixation of iodine by organic soil compounds appears to be dependent upon microbiological activity, because sterilization by heating or radiation commonly results in much lower iodine retention (Bunzl and Schimmack, 1988;Koch et al, 1989;Muramatsu et al, 1990;Bors et al, 1991;Rädlinger and Heumann, 2000).…”
Section: Imentioning
confidence: 99%